BILATERAL SIMULTANEOUS FRACTURES NECK OF FEMUR: A CASE REPORT AND REVIEW OF LITERATURE - Iqbal, Malik Javed; Inam, Muhammad; Khan, Mumtaz; Ashfaq, Muhammad (Journal of Postgraduate Medical Institute, 2011)
We report a case in an elderly lady who had an epileptic convulsion and sustained bilateral simultaneous fracture neck of femur. This lady was deaf and dumb and the diagnosis was therefore delayed. The patient was initially diagnosed as flaccid paralysis and was kept under observation. After 36 hours, x-rays of hip and dorsolumber spine was done that showed bilateral simultaneous fractures of hip. Both fractures were treated with bilateral modular hip hemiarthroplasties within 24 hours of diagnosis. She made uneventful recovery.